Practice patterns of obstetric care in twin gestations: the value of MFM consultation. (17th September 2022) - Adra, Abdallah; Khalife, Dalia; Usta, Ihab M.; Hobeika, Elie; Mirza, Fadi; Ghulmiyyah, Labib; Nassar, Anwar H.
Abstract: Objectives: To evaluate the practice patterns among Lebanese obstetricians regarding obstetric care of twins and to compare selected practice patterns between general obstetricians and maternal fetal medicine physicians. Methods: Questionnaires distributed during the annual meeting of the Lebanese Society of Obstetrics and Gynecology. Results: Questionnaires were returned by 69.2% of the 296 physicians approached. Ten percent had fellowship training in Maternal Fetal Medicine (MFM). Thirty-nine percent perform cervical length measurement at 20–24 weeks of gestation and 34% recommend vaginal progesterone in case of a short cervix. When comparing selected practice patterns between MFM & general obstetricians, MFM specialists were less likely to perform cervical cerclage in the first trimester (5.9% versus 49%, p  = .001), more likely to offer prenatal screening for aneuploidy (66.6% vs 46.4%, p  = .03), less likely to use vaginal progesterone in the second trimester in the case of a short cervix (42.1% vs 61.8%, p  = .04), less likely to perform serial ultrasound exam in the third trimester to assess fetal growth (50% vs 78%, p  = .005) and more likely to deliver monoamniotic twins at 32–34 weeks of gestation (55% vs 37%, p  = .05). Conclusion: Because of the different background of the Lebanese physicians, MFM specialists are more likely to follow obstetric care guidelines in twin gestation.